The Antecedents of Positive Word of Mouth and Revisit Intention of Thai Tourists Traveling to Ecotourism Attractions in Thailand - Jaitip, Chotika; Sawang, Sumalee (Rajapark Journal, 2024)
This research aims to 1) develop a causal relationship model of antecedents of positive word of mouth and revisit intention of Thai tourists traveling to ecotourism attractions in Thailand and 2) validate consistency of a causal relationship model of antecedents of positive word of mouth and revisit intention of Thai tourists traveling to ecotourism attractions in Thailand with empirical data. The sample was 511 Thai tourists traveling to ecotourism attractions in Thailand. They were selected by quota sampling. The instrument for collecting data was a questionnaire. Data analysis is done using descriptive statistics (frequency distribution, percentage, mean, and standard deviation) and inferential statistics (structural equation modeling). The research results were found as follows; 1.1) perceived electronic word of mouth, social media usage, and novelty seeking, which had a positive and direct influence on the memorable experience of Thai tourists; 1.2) perceived electronic word of mouth, social media usage, novelty seeking, and memorable experiences had a positive and direct influence on the destination trust of Thai tourists; 1.3) the memorable experiences and destination trust had a positive and direct influence on the life satisfaction of Thai tourists; 1.4) the memorable experiences, destination trust, and life satisfaction had a positive and direct influence on the positive word of mouth of Thai tourists; 1.5) the memorable experiences, destination trust, and life satisfaction had a positive and direct influence on the revisit intention of Thai tourists; and a causal relationship model of antecedents of positive word of mouth and revisit intention of Thai tourists traveling to ecotourism attractions in Thailand was consistent with empirical data.